River conversations: A confluence of lessons and emergence from the Taieri River and the Nechako River. (30th December 2021) - Parkes, Margot W.
Abstract: Drawing on ongoing patterns of learning and relationship, this paper offers a reflection and acknowledgement on the notable influence of two rivers and their role as respected and highly valued "eco‐social elders": The Taieri River in Otago, New Zealand, and the Nechako River in northern British Columbia, Canada. The paper is motivated by the question: " If a river has 'voice', what can be learned from the emergence arising from rivers 'in conversation'? ". At the heart of the reflection are the themes of confluence and emergence—ways in which we grasp the coming together of things, especially when that combination is more than the sum of their parts. The paper aims to explore a "conversation" between the river teachings of the Taieri River and the Nechako River, identifying examples of patterns and connections between distinct river "voices, " and how these may contribute to emergence and ongoing conversations among different rivers and their teachings. The paper commences with an introduction to both rivers, identifying points of direct comparison and contrast, then moving to explore themes of confluence, weaving and emergence, combining ecological, metaphorical, and personal perspectives. The conversation then progresses downstream to river–ocean relationships, reflecting on rivers as eco‐social elders that inspire conversations, provide a sense of home, and offer a point of reference to consider the wider influence on rivers and waterways on the health of diverse species within catchments and across the planet.